Sociocultural data to accomplish Department of Defense missions toward a unified social framework : workshop summary - National Research Council (U.S.); Pool, Robert; National Research Council (U.S.). Planning Committee on Unifying Social Frameworks; National Research Council (U.S.). Board on Human-Systems Integration; National Research Council (U.S.). Division of Behavioral and Social Sciences and Education (National Academies Press, 2011)
Summarizes presentations and discussions that took place on August 16-17, 2010, at a National Research Council public workshop sponsored by the Office of Naval Research. The workshop addressed the variables and complex interaction of social and cultural factors that influence human behavior, focusing on potential applications to the full spectrum of military operations. The workshop's keynote address by Major General Michael T. Flynn, U.S. Army, provided critical context about the cultural situation and needs of the military operating in Afghanistan. Additional presentations were divided into four panels to address the diverse missions encountered by the U.S. military worldwide. The workshop concluded with a final panel to discuss the strengths and weaknesses of different methods of acquiring and using relevant data and knowledge to accomplish these missions.
Keywords: United States : Dept. of Defense : Research : Congresses; Social sciences : Research : Congresses; United States : Armed Forces : Operational readiness : Congresses